2019
DOI: 10.1152/ajprenal.00100.2019
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of uremic solutes in the cerebrospinal fluid in experimental acute renal failure

Abstract: The accumulation of uremic solutes in kidney failure may impair mental function. The present study profiled the accumulation of uremic solutes in the cerebrospinal fluid (CSF) in acute renal failure. CSF and plasma ultrafiltrate were obtained from rats at 48 h after sham operation (control; n = 10) or bilateral nephrectomy ( n = 10) and analyzed using an established metabolomic platform. Two hundred forty-eight solutes were identified as uremic based on their accumulation in the plasma ultrafiltrate of nephrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Indeed, pre-clinical studies have suggested that levels of many uraemic solutes are normally kept in low concentration in the CSF (relative to the plasma ultrafiltrate) by the action of the BBB and blood–CSF barriers. These barriers remain functional when the kidney function fails but cannot prevent the accumulation of uraemic solutes in the CSF [ 60 ]. Under normal conditions, the concentration of IS in the brain is reportedly 3.4 times lower than in the serum [ 60 ].…”
Section: Direct Effects Of Uraemic Toxins On the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, pre-clinical studies have suggested that levels of many uraemic solutes are normally kept in low concentration in the CSF (relative to the plasma ultrafiltrate) by the action of the BBB and blood–CSF barriers. These barriers remain functional when the kidney function fails but cannot prevent the accumulation of uraemic solutes in the CSF [ 60 ]. Under normal conditions, the concentration of IS in the brain is reportedly 3.4 times lower than in the serum [ 60 ].…”
Section: Direct Effects Of Uraemic Toxins On the Brainmentioning
confidence: 99%
“…These barriers remain functional when the kidney function fails but cannot prevent the accumulation of uraemic solutes in the CSF [ 60 ]. Under normal conditions, the concentration of IS in the brain is reportedly 3.4 times lower than in the serum [ 60 ]. Although the source of IS in the brain has not been identified, this limited distribution might be due to the brain-to-blood transfer of IS by the organic anion transporter (OAT) at the BBB [ 58 ].…”
Section: Direct Effects Of Uraemic Toxins On the Brainmentioning
confidence: 99%
“…A study conducted in rats investigated the integrity of the BBB 48 hours after bilateral nephrectomy. 73 Uremic retention solutes were identified in the blood of these animals and 124 of these solutes were detected in the CSF. When kidney function was normal, the CSF/plasma ratio of 31 out of 124 solutes was less than 25%), pointing to a restriction in diffusion across the BBB.…”
Section: Effects Of Kidney Insufficiency On Neurotransmitters and Brain Structurementioning
confidence: 94%
“…However, the CSF/plasma ratio was reduced for the majority of the, showing that restriction of diffusion across the BBB, and possibly a partial saturation of transport of some solutes via specific transporters. 73 Thus, it is unclear if uremia itself induces disruption of the BBB. However, in two more gradually developing models of CKD (adenine rich diet and 5/6 nephrectomy models), uremia increased BBB permeability as assessed by radioisotopes.…”
Section: Effects Of Kidney Insufficiency On Neurotransmitters and Brain Structurementioning
confidence: 99%
“…It should be emphasized, these changes were absent in rats with isolated liver injury, which suggest that different effects originate according to the injured organ [ 80 ]. In rats undergoing bilateral nephrectomy, the main solutes that accumulate in CSF included IS, hippurate, TMAO and myo-inositol [ 81 ]. Studies in humans with AKI are scarce, however, in a population-based cohort study, AKI was found to increase the risk for dementia with a hazard ratio of 1.88 (95% CI 1.76–2.01) after adjustment for sex, age and comorbidities [ 82 ].…”
Section: Medium Molecular Weight Moleculesmentioning
confidence: 99%